The Impact of the Realistic Mathematics Education (RME) Learning Model on Students' Understanding of Mathematical Concepts - Netriwati, Netriwati; Negara , Hasan Sastra; Tirani, Kinanti Senja (JURNAL PENDIDIKAN DASAR NUSANTARA, 2025)
Several previous studies have applied the Realistic Mathematics Education learning model, but few have linked this research to simple spatial geometry material. The study looked at the differences in the influence of the Realistic Mathematics Education learning model on students' understanding of mathematical concepts. The type of research is Quasi Experimental Design with a quantitative method as a sample representing 47 students of class V SDN 2 Way Gubag Bandar Lampung. The instrument used was an essay test, the results of the normality and homogeneity tests showed that both samples were normally distributed and homogeneous. The findings of the analysis using the t-test. It can be concluded that the sig value (2-tailed) is 0.00 <0.05, then it is accepted and rejected so that there is a significant difference in students' understanding of the concept. Which means that there is an influence of the Realistic Mathematics Education (RME) learning model on students' understanding of mathematical concepts in class V SDN 2 Way Gubag Bandar Lampung. So it can be recommended as an effective learning model in learning Mathematics.